A Linear Stability Analysis of a Homogeneous Fluidized Bed - SOBRAL, Y.D.; CUNHA, F.R. (Trends in Computational and Applied Mathematics, 2002)
In this work the local equations governing the dynamics of fluidized beds are written in terms of averaged variables and constitutive relations based on physical arguments are proposed. The averaged equations are perturbed with small disturbances from the homogeneous fluidization state, and linearized with respect to the perturbations. A stability analysis is carried out and shows that the particle pressure term has a stabilizing effect and that the particle viscosity acts as a short wave filter. The behavior of the primary instabilities described by the proposed model is in qualitative agreement with experimental observations.